Feasibility Analysis of Cassava and Glucose Syrup as Alternatives Raw Materials for Industrial Nata (Case Study at CV. Agrindo Suprafood, Yogyakarta) - Jumeri Jumeri; Persia Manggala; Ariesta Cintiadewi; Nafis Khuriyati; Didik Purwadi (Agroindustrial Journal, 2017)
CV Agrindo Suprafood as one of the largest suppliers of nata de coco in Yogyakarta is only able to meet 40% of market demand due to the limitations of coconut water. An alternative strategy to tackle this problem is by looking for coconut water substitute as raw material for the production of nata. The purpose of this study was to analyze the potential of cassava and glucose syrup as raw material alternative of nata and its feasibility on an industrial scale . Formulation of nata is performed on a pilot plant scale with cassava and glucose syrup as raw material. Cassava glucose and glucose syrup were separately used as a growth medium of Acetobacter xylinum for the production of nata. The physical, chemical, and sensory evaluation as well as technical and financial feasibility analysis were conducted on the nata product. The best formula for production of nata de cassava and nata de glucose was obtained by a combination of glucose, glucose syrup, coconut water, ZA,vinegar, and acetic acid. Based on the analysis, it was concluded that both of nata production were industrially-feasible in terms of both technical and financial analysis. However, based on the financial analysis, nata de glucose was more prospective than nata de cassava.